PbS-doped glass for solar blind detection and preparation method and application of PbS-doped glass
By using PbS doped glass materials in the sun blind detector, the characteristics of PbS clusters absorb and convert sun blind light are used to absorb and convert sun blind light, and the problem of existing detectors being easily disturbed is solved, achieving a high-impact sun blind light detection effect.
Patent Information
- Application Number
- CN202411861387.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
AI Technical Summary
Existing sun blind detector materials are susceptible to interference from non-sun blind light during detection, resulting in poor anti-interference ability and making it difficult to accurately detect sun blind light signals.
PbS doped glass is used as the detection material, and by forming PbS clusters in the glass, absorbing sunblind light and converting it into visible light, the detection of sunblind light is achieved by using a silicon detector. The wavelength of the luminescence center of the PbS cluster corresponds one by one to the excitation light wavelength, which can effectively eliminate interference from other lights.
It realizes high anti-interference sun blind light detection, which can accurately identify sun blind light signals, reduces the impact of non-sun blind light interference, and improves the sensitivity and accuracy of detection.
Smart Images

Figure CN119774871A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of doped glass, and in particular relates to PbS-doped glass for solar-blind detection, a preparation method thereof, and applications thereof. Background Art
[0002] Solar-blind light refers to ultraviolet light with a wavelength between 180 and 280 nm. Because ozone and water vapor in Earth's atmosphere strongly absorb solar-blind light, it cannot pass through the atmosphere to reach the Earth's surface. Detecting solar-blind light signals on the Earth's surface undoubtedly indicates the occurrence of specific events such as missile launches, explosive detonations, and fires. Therefore, monitoring solar-blind signals is extremely important.
[0003] Solar-blind light has many advantages over visible and infrared light. For example, solar-blind light detection offers strong anti-interference capabilities, high sensitivity, and low noise. Solar-blind light detection has important applications in areas such as atmospheric ultraviolet environment monitoring, high-speed missile detection, and fire flame detection. With the development of society, people are pursuing detectors with higher accuracy, a wider response range, low cost, and high sensitivity. Photoelectric detection materials are crucial in solar-blind light detectors. Traditional detectors use single crystals such as gallium oxide as photoelectric conversion materials to directly detect solar-blind light. The preparation of single crystal materials is complex and costly, and the response range of gallium oxide crystals is limited to around 250nm, a relatively narrow range. In recent years, indirect solar-blind light detectors based on rare-earth ion-doped glass have been developed. These detectors use rare-earth-doped microcrystalline glass as the photoconversion material, converting absorbed solar-blind light into visible light. The visible light signal is then received by a silicon detector and converted into an electrical signal, enabling solar-blind light detection. Glass has high optical transmittance and low production cost, while rare-earth ions have high luminescence efficiency and a response range that covers the entire solar-blind to visible light region. Rare earth ion-doped glass is a highly sensitive, wide-range, solar-blind detection material. However, the emission spectrum of rare earth ion-doped materials is fixed and insensitive to excitation wavelengths. Besides solar-blind light, long-wavelength ultraviolet light (>280nm) and even blue light can excite rare earth ions, producing visible light with the same spectrum. This results in poor anti-interference capabilities for detectors, making it easy for them to mistake visible light for solar-blind light signals, leading to false detections. Summary of the Invention
[0004] To overcome the shortcomings and deficiencies of the aforementioned prior art, the primary objective of the present invention is to provide a PbS-doped glass for solar-blind detection that features low production cost, a wide detection range, wavelength identification, and high interference resistance. The PbS-doped glass absorbs solar-blind light and emits visible luminescence, which, when received by a silicon detector, enables solar-blind light detection. More importantly, the central luminescence wavelength of the PbS-doped glass corresponds exactly to the wavelength of the excitation light, effectively eliminating the influence of other light sources and detecting only the solar-blind light. This provides a novel detection material for the preparation of highly interference-resistant solar-blind detectors.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned PbS-doped glass for solar-blind detection.
[0006] Another object of the present invention is to provide an application of the above-mentioned PbS-doped glass for solar-blind detection.
[0007] The purpose of the present invention is achieved through the following solutions:
[0008] A PbS-doped glass for solar-blind detection comprises base glass and PbS, wherein the molar amount of PbS accounts for 0.01 to 5.0% of the total molar amount of the base glass and PbS. The molar amount of the base glass is the total molar amount of the raw materials of the base glass.
[0009] Preferably, the molar amount of PbS accounts for 0.1-2.0% of the total molar amount of the matrix glass and PbS.
[0010] The glass matrix comprises one of silicate glass, germanate glass, borate glass, fluorosilicate glass and phosphate glass;
[0011] Preferably, the silicate glass comprises the following components in molar percentages:
[0012] SiO2: 30~75%;
[0013] B2O3: 10-30%;
[0014] Na2O: 10-20%;
[0015] ZnO: 5-20%;
[0016] Preferably, the germanate glass comprises the following components in molar percentages:
[0017] GeO2: 50~89%;
[0018] Ga2O3: 5~25%;
[0019] BaO: 5-20%;
[0020] La2O3: 1~5%;
[0021] Preferably, the borate glass comprises the following components in molar percentages:
[0022] B2O3: 50~90%;
[0023] ZnO: 4-20%;
[0024] Na2O: 5-25%;
[0025] Al2O3: 1~5%;
[0026] Preferably, the fluorosilicate glass comprises the following components in molar percentages:
[0027] SiO2: 40~84%;
[0028] NaF: 5-30%;
[0029] ZnF2: 10-25%;
[0030] AlF3: 1-5%;
[0031] Preferably, the phosphate glass comprises the following components in molar percentages:
[0032] P2O5: 50-79%;
[0033] K2O: 10-25%;
[0034] BaO: 10-20%;
[0035] Al2O3: 1~5%.
[0036] A method for preparing the above-mentioned PbS-doped glass for solar-blind detection comprises the following steps:
[0037] Powdered raw materials are weighed according to the formula of the glass matrix, and then evenly mixed with PbS. The resulting mixture is melted at high temperature and stirred and homogenized during the melting process. The material is formed into a block glass sample, thus obtaining PbS-doped glass for solar-blind detection.
[0038] The purity of the powdered raw material is preferably greater than or equal to 99%, more preferably 99.9%;
[0039] The high temperature melting refers to keeping the temperature at 900-1650℃ for 0.5-3h;
[0040] The obtained bulk glass samples also need to be annealed, that is, the bulk glass samples after being formed are immediately placed in an annealing furnace for heat preservation treatment. The annealing temperature is 300-700°C and the annealing time is 0.5-5h.
[0041] The above-mentioned PbS-doped glass for solar-blind detection is used in solar-blind light detection.
[0042] A solar-blind detector is prepared by using prepared PbS-doped glass as a detection material, fixing the prepared PbS-doped glass on a silicon photodetector to prepare the solar-blind detector.
[0043] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0044] (1) The present invention uses PbS-doped glass as a solar-blind detection material. PbS forms clusters in the glass, eliminating the need for crystallization, resulting in high glass transmittance and low cost. More importantly, the PbS clusters absorb light from the entire solar-blind region, converting it into visible light that can be detected by silicon photodetectors, enabling solar-blind light detection.
[0045] (2) Currently, the emission wavelength of rare earth ion-doped detection glass is fixed, and it is impossible to eliminate interference from non-solar-blind light in the environment. The absorption peak of PbS clusters covers the entire solar-blind light region, and the emission peak wavelength shifts with changes in the wavelength of the excitation light. In this way, the peak position of the excitation light can be inferred from the emission spectrum, thereby eliminating interference from non-solar-blind light and obtaining a solar-blind light detector with high interference resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is the luminescence spectrum of PbS-doped glass in Example 1.
[0047] Figure 2 This is the solar-blind photoelectric response diagram of the PbS-doped glass in Example 1. DETAILED DESCRIPTION
[0048] The present invention will be described in further detail below with reference to the Examples and accompanying drawings, but the embodiments of the present invention are not limited thereto. Where specific conditions are not specified in the Examples, conventional conditions or conditions recommended by the manufacturer were followed. Reagents or instruments used, where the manufacturer is not specified, are commercially available conventional products.
[0049] Example 1
[0050] (1) The PbS-doped glass adopts the following formula, where the percentages refer to molar percentages:
[0051] SiO2: 49.9%;
[0052] B2O3: 20%;
[0053] Na2O: 20%;
[0054] ZnO: 10%;
[0055] PbS: 0.1%.
[0056] (2) Weigh 100 g of high-purity powdered raw materials according to the component formula and mix them thoroughly in an agate mortar.
[0057] (3) Pour the evenly mixed material into a 150 ml alumina crucible, cover it with an alumina lid, place it in an electric furnace, slowly heat it to 1200 ° C and keep it warm for 30 minutes, then add a stirring rod and stir it slowly (10 revolutions per minute) for 30 minutes, keep it warm for another 30 minutes, discharge the material, and shape it into a square long strip glass sample.
[0058] (4) Immediately place the glass in an annealing furnace and keep it at 400℃ for 2 hours to eliminate some stress.
[0059] (5) Test the emission spectra under different excitation wavelengths to characterize the luminescence performance of the glass. Figure 1 The following is a graph showing the luminescence spectrum of PbS-doped glass. As can be seen, when the excitation wavelength is adjusted from 200 to 358 nm, the PbS-doped glass exhibits broadband luminescence, and the central wavelength of the luminescence peak shifts with the excitation wavelength. Interestingly, the shape of the luminescence spectrum is completely different when the excitation wavelength is below 280 nm than when it is above 280 nm. Therefore, the emission spectrum can accurately determine the excitation wavelength, thereby eliminating interference from non-solar-blind light.
[0060] (6) The prepared PbS-doped glass was fixed on a silicon photodetector to prepare a solar-blind light detector and the photoelectric performance of the detector was tested. The detection response curve of the detector was as follows: Figure 2 As shown, the detector has a good response in the solar-blind light band, indicating that PbS-doped glass has important application significance in the preparation of solar-blind photodetectors.
[0061] Example 2
[0062] (1) The glass adopts the following formula, where the percentages refer to molar percentages:
[0063] GeO2: 70.5%;
[0064] Ga2O3: 15%;
[0065] BaO: 10%;
[0066] La2O3: 4%;
[0067] PbS: 0.5%;
[0068] (2) Weigh 100 g of high-purity powdered raw materials according to the component formula and mix them thoroughly in an agate mortar.
[0069] (3) Pour the evenly mixed material into a 150 ml alumina crucible, cover it with an alumina lid, place it in a low-temperature electric furnace, slowly heat it to 1350 ° C and keep it warm for 30 minutes, then add a stirring rod and stir it slowly (10 revolutions per minute) for 30 minutes, keep it warm for another 60 minutes, discharge the material, and shape it into a square long strip glass sample.
[0070] (4) Immediately place the glass in an annealing furnace and keep it at 510℃ for 2 hours to eliminate some stress.
[0071] (5) Test the emission spectra under different excitation wavelengths to characterize the luminescence performance of the glass.
[0072] (6) The prepared PbS-doped glass was fixed on a silicon photodetector to prepare a solar-blind light detector, and the photoelectric performance of the detector was tested.
[0073] Example 3
[0074] (1) The glass adopts the following formula, where the percentages refer to molar percentages:
[0075] B2O3: 69.5%;
[0076] ZnO: 10%;
[0077] Na2O: 15%;
[0078] Al2O3: 4%;
[0079] PbS: 1.5%;
[0080] (2) Weigh 100 g of high-purity powdered raw materials according to the component formula and mix them thoroughly in an agate mortar.
[0081] (3) Pour the evenly mixed material into a 150 ml alumina crucible, cover it with an alumina lid, place it in a low-temperature electric furnace, slowly heat it to 950 ° C and keep it warm for 30 minutes, then add a stirring rod and stir it slowly (10 revolutions per minute) for 30 minutes, keep it warm for another 60 minutes, discharge the material, and shape it into a square long strip glass sample.
[0082] (4) Immediately place the glass in an annealing furnace and keep it at 350℃ for 2 hours to eliminate some stress.
[0083] (5) Test the emission spectra under different excitation wavelengths to characterize the luminescence performance of the glass.
[0084] (6) The prepared PbS-doped glass was fixed on a silicon photodetector to prepare a solar-blind light detector, and the photoelectric performance of the detector was tested.
[0085] Example 4
[0086] (1) The glass adopts the following formula, where the percentages refer to molar percentages:
[0087] SiO2: 60.5%;
[0088] NaF: 20%;
[0089] ZnF2: 15%;
[0090] AlF3: 4%;
[0091] PbS: 0.5%;
[0092] (2) Weigh 100 g of high-purity powdered raw materials according to the component formula and mix them thoroughly in an agate mortar.
[0093] (3) Pour the evenly mixed material into a 150 ml alumina crucible, cover it with an alumina lid, place it in a low-temperature electric furnace, slowly heat it to 1500 ° C and keep it warm for 30 minutes, then add a stirring rod and stir it slowly (10 revolutions per minute) for 30 minutes, keep it warm for another 60 minutes, discharge the material, and shape it into a square long strip glass sample.
[0094] (4) Immediately place the glass in an annealing furnace and keep it at 420℃ for 2 hours to eliminate some stress.
[0095] (5) Test the emission spectra under different excitation wavelengths to characterize the luminescence performance of the glass.
[0096] (6) The prepared PbS-doped glass was fixed on a silicon photodetector to prepare a solar-blind light detector, and the photoelectric performance of the detector was tested.
[0097] Example 5
[0098] (1) The glass adopts the following formula, where the percentages refer to molar percentages:
[0099] P2O5: 62%;
[0100] K2O: 18%;
[0101] BaO: 15%;
[0102] Al2O3: 3%;
[0103] PbS: 20%;
[0104] (2) Weigh 100 g of high-purity powdered raw materials according to the component formula and mix them thoroughly in an agate mortar.
[0105] (3) Pour the evenly mixed material into a 150 ml alumina crucible, cover it with an alumina lid, place it in a low-temperature electric furnace, slowly heat it to 1250 ° C and keep it warm for 30 minutes, then add a stirring rod and stir it slowly (10 revolutions per minute) for 30 minutes, keep it warm for another 60 minutes, discharge the material, and shape it into a square long strip glass sample.
[0106] (4) Immediately place the glass in an annealing furnace and keep it at 540℃ for 2 hours to eliminate some stress.
[0107] (5) Test the emission spectra under different excitation wavelengths to characterize the luminescence performance of the glass.
[0108] (6) The prepared PbS-doped glass was fixed on a silicon photodetector to prepare a solar-blind light detector, and the photoelectric performance of the detector was tested.
[0109] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.
Claims
1. A PbS-doped glass for solar-blind detection, characterized in that The invention comprises a base glass and PbS, wherein the molar amount of PbS accounts for 0.01 to 5.0% of the total molar amount of the base glass and PbS.
2. The PbS-doped glass for solar-blind detection according to claim 1, characterized in that: The molar amount of PbS accounts for 0.1-2.0% of the total molar amount of the base glass and PbS.
3. The PbS-doped glass for solar-blind detection according to claim 1, characterized in that: The glass matrix comprises one of silicate glass, germanate glass, borate glass, fluorosilicate glass and phosphate glass.
4. The PbS-doped glass for solar-blind detection according to claim 3, characterized in that: The silicate glass comprises the following components in molar percentage: SiO2: 30-75%; B2O3: 10-30%; Na2O: 10-20%; ZnO: 5-20%; The germanate glass comprises the following components in molar percentage: GeO2: 50~89%; Ga2O3: 5-25%; BaO: 5-20%; La2O3: 1-5%; The borate glass comprises the following components in molar percentage: B2O3: 50~90%; ZnO: 4-20%; Na2O: 5-25%; Al2O3: 1-5%; The fluorosilicate glass comprises the following components in molar percentage: SiO2: 40-84%; NaF: 5-30%; ZnF2: 10-25%; AlF3: 1-5%; The phosphate glass comprises the following components in molar percentage: P2O5: 50-79%; K2O: 10-25%; BaO: 10-20%; Al2O3: 1~5%.
5. A method for preparing PbS-doped glass for solar-blind detection according to any one of claims 1 to 4, characterized in that The following steps are involved: Powdered raw materials are weighed according to the formula of the glass matrix, and then evenly mixed with PbS. The resulting mixture is melted at high temperature, stirred and homogenized during the melting process, and the material is formed into a block glass sample to obtain PbS-doped glass for solar-blind detection.
6. The method for preparing PbS-doped glass for solar-blind detection according to claim 5, characterized in that: The high temperature melting refers to keeping the temperature at 900-1650°C for 0.5-3h.
7. The method for preparing PbS-doped glass for solar-blind detection according to claim 5, characterized in that: The obtained bulk glass sample is also subjected to annealing treatment, that is, the bulk glass sample after being formed is immediately placed in an annealing furnace for heat preservation treatment, the annealing temperature is 300-700° C., and the annealing time is 0.5-5h.
8. Use of the PbS-doped glass for solar-blind detection according to any one of claims 1 to 4 in solar-blind light detection.
9. A solar-blind detector, which uses the PbS-doped glass according to claim 8 as a detection material and fixes it on a silicon photodetector to prepare a solar-blind detector.
Citation Information
Patent Citations
Quantum dot doped glass and preparation method thereof
CN104230167A
Narrow-particle size distribution PbS quantum dot-doped glass and preparation method thereof
CN106966591A
Microcrystalline glass doped with quantum dots and rare earth and preparation method thereof
CN108863083A
Diffraction optical element and glass material
JP2005321421A
Fabrication method of silicate glass including lead sulfide quantum dots containing rare earth metal
KR1020120097832A